Экология и хозяйственное значение листоеда гречишного (Gastrophysa potygoni L.) на Украине - Бровдий, В.М. (Вестник зоологии, 1976)
Gastrophysa polygoni L. is distributed in the whole territory of the Ukraine, including the mountain regions of the Crimea and Carpathians. In the republic it is an ordinary species that multiplies intensively on the wild-growing grassy plants of the Polygonaceae family. From them it migrates to the field crops, affecting them significantly. The evidence are given on the development cycle, phenology, trophic relations, fertility, entomophages and economic significance of the species.